Optimization of Zakat, Infaq, and Shadaqah Management in Bojongmalang Village, Cimaragas District - Mujib, Haqibul; Aminullah, Rifqi Arief; Endang, Ujang; Hamidah, Wanda; Nurhidayah, Sifa Fathul (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2024)
The importance of managing zakat, infaq and shadaqoh funds makes the government continue to empower by issuing various laws and regulations regarding ZIS management so that the objectives of ZIS management can be optimized. But in reality until now, with the number of institutions that manage zakat and various provisions that have been determined have not been able to achieve the potential of zakat in Indonesia, this can be caused by an obstacle in carrying out management at the City, District to Village or Kelurahan level. The obstacles experienced in Bojongmalang Village in managing zakat, infaq and shadaqoh funds are that the community is not yet aware of the importance of zakat, infaq and shadaqoh to UPZ, then does not understand how the potential of ZIS can solve problems in the community, and the local government of Bojongmalang Village is not in sync with UPZ and MUI and their leaders, which results in the potential of ZIS which should be large but still minimal. The purpose of this community service is to conduct socialization in collaboration with BAZNAS Ciamis Regency to provide broad knowledge about optimizing ZIS management to create Muslim awareness of the obligation to pay zakat and encourage positive attitudes of Muslims towards zakat, infaq, shadaqoh.